2021
DOI: 10.1161/jaha.120.017932
|View full text |Cite
|
Sign up to set email alerts
|

Electroanatomic Ratios and Mortality in Patients With Heart Failure: Insights from the ASIAN‐HF Registry

Abstract: Background QRS duration (QRSd) is a marker of electrical remodeling in heart failure. Anthropometrics and left ventricular size may influence QRSd and, in turn, may influence the association between QRSd and heart failure outcomes. Methods and Results Using the prospective, multicenter, multinational ASIAN‐HF (Asian Sudden Cardiac Death in Heart Failure) registry, this study evaluated whether electroanatomic ratios (QRSd indexed for heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…We didn't find postoperative LVEDD has a significant difference between these patients (47.06 ± 6.85 vs 49.02 ± 7.46 mm, p = 0.101). Differences in left ventricular size is postulated to contribute to variations of QRS with sex, race and obesity [ 20 ]. QRS duration can be normalized to left ventricular dimension to adjust for ventricular conduction path length, result in a measure of conduction velocity of myocardial [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We didn't find postoperative LVEDD has a significant difference between these patients (47.06 ± 6.85 vs 49.02 ± 7.46 mm, p = 0.101). Differences in left ventricular size is postulated to contribute to variations of QRS with sex, race and obesity [ 20 ]. QRS duration can be normalized to left ventricular dimension to adjust for ventricular conduction path length, result in a measure of conduction velocity of myocardial [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analyses showed that QRS/LVEDD was stable in each subgroup, which indicated that QRS/LVEDD was a predictor which would not influence by gender, aging, BMI or types of surgery. In previously studies, Chyou JY et al has found that indexing of QRS to LVEDV can predict mortality in patients with heart failure with preserved ejection fraction (HFrEF) with nonischemic cardiomyopathy [ 20 ], and strongly correlated with cardiac resynchronization therapy [ 14 ]. The mechanism underlying is complex and multifactorial, with several potential pathway implicated.…”
Section: Discussionmentioning
confidence: 99%
“…Increased electrocardiographic QRSd is a marker of myocardial/ electrical remodeling, structural changes and increased TDR in the myocardium. 8 Recent studies have shown that structural changes in the myocardium, including myocyte hypertrophy and fibrosis, occur simultaneously in the atria and ventricles. Therefore, an increased QRS duration is considered indicative of ventricular and supraventricular arrhythmias.…”
Section: Introductionmentioning
confidence: 99%